2006
DOI: 10.2503/jjshs.75.256
|View full text |Cite
|
Sign up to set email alerts
|

Breeding of Carnations (Dianthus caryophyllus L.) for Long Vase Life and Rapid Decrease in Ethylene Sensitivity of Flowers after Anthesis

Abstract: Genetic improvement of flower vase life is an important breeding target. A breeding program aimed to improve the vase life of carnations (Dianthus caryophyllus L.) that carried out by repeatedly crossing and selecting promising progenies was effective. Thus, we developed many carnation lines with extremely long vase life by using the conventional cross-breeding technique. Selected lines from second-, third-and fourthgeneration have vase lives that are 2.7 to 4.1 times longer than the control cultivar, 'White S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…We selected a total of 123 lines (including 2 cultivars, 'Miracle Rouge' and 'Miracle Symphony') with improved vase life by conventional breeding techniques (Table 1). The crossing and selection resulted in dramatic alterations in the flower vase life of each generation and particularly in ethylene production of many selected lines (Onozaki et al, 2001(Onozaki et al, , 2006b(Onozaki et al, , 2011.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We selected a total of 123 lines (including 2 cultivars, 'Miracle Rouge' and 'Miracle Symphony') with improved vase life by conventional breeding techniques (Table 1). The crossing and selection resulted in dramatic alterations in the flower vase life of each generation and particularly in ethylene production of many selected lines (Onozaki et al, 2001(Onozaki et al, , 2006b(Onozaki et al, , 2011.…”
Section: Discussionmentioning
confidence: 99%
“…We then crossed and selected promising offspring with long vase life for seven generations, from 1992 to 2008, in order to improve the vase life of carnation flowers. The populations that we used in the present study were the same offspring populations over generations as reported previously (Onozaki et al, 2001(Onozaki et al, , 2006b(Onozaki et al, , 2011. Here we use the term "first generation", "second generation", "third generation", "fourth generation", "fifth generation", "sixth generation", and "seventh generation" in place of "parental generation", "first generation", "second generation", "third generation", "fourth generation", "fifth generation", and "sixth generation" described in the previous papers.…”
Section: Crossing and Selectionmentioning
confidence: 99%
See 3 more Smart Citations